Application of the feedback mechanism in systems using a direct current motor - Stavtsev Dmitry; Provorny Ivan; Chumakov Ivan; Pokushko Mariia; Nikiforov Artur (ITM Web of Conferences)
This article focuses on the study and modeling of an electric drive control system using a feedback mechanism. It explores the mathematical models of direct current motor operation under varying load conditions, including the description of patterns of current and angular speed. Special attention is given to algorithm for regulating control voltage and angular speed, as well as their impact on the system's dynamics. The paper presents the results of computer simulations and analyzes transitional processes in various operating modes, including abrupt and gradual load changes. Based on the simulations, conclusions were drawn about the stability and efficiency of the proposed control methods and their adaptability to enhance overall system reliability.